2008
DOI: 10.1162/isec.2008.32.3.113
|View full text |Cite
|
Sign up to set email alerts
|

Great Powers and Hierarchical Order in Southeast Asia: Analyzing Regional Security Strategies

Abstract: The small and medium-sized states in Southeast Asia have faced significant geostrategic changes with the end of the Cold War and the rise of China. Over the last decade, scholars have debated how these countries would cope with growing Chinese power, and how their relations with the other major powers in the region would change. Some analysts have suggested that the region is shifting toward a more China-centered order, but this view is premature. Eschewing the simple dichotomy of balancing versus bandwagoning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
121
0
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 297 publications
(128 citation statements)
references
References 47 publications
0
121
0
7
Order By: Relevance
“…Scholars have described these strategies of regional architecture-building and efforts to keep the United States engaged while ensuring other regional powers are involved as "omni-enmeshment" and "soft balancing." 169 There is indeed some empirical evidence for the growth of multilateralism and even defense regionalism in the postCold War and post-Asian financial crisis periods. 170 In other words, Southeast Asian states simply gave up on trying to militarily balance against China in the post-Cold War era and instead opted to focus on diplomatic engagement strategies.…”
Section: What Southeast Asian States Spend Their Defense Budgets Onmentioning
confidence: 99%
“…Scholars have described these strategies of regional architecture-building and efforts to keep the United States engaged while ensuring other regional powers are involved as "omni-enmeshment" and "soft balancing." 169 There is indeed some empirical evidence for the growth of multilateralism and even defense regionalism in the postCold War and post-Asian financial crisis periods. 170 In other words, Southeast Asian states simply gave up on trying to militarily balance against China in the post-Cold War era and instead opted to focus on diplomatic engagement strategies.…”
Section: What Southeast Asian States Spend Their Defense Budgets Onmentioning
confidence: 99%
“…The re-emergence of China as a great power in the Indo-Pacific motivated nearly every state in the region to attempt to socialize China into the existing normative order (Goh 2007;Johnston 2008). ASEAN was among the principal players in this socializing effort, particularly as the Chinese military modernization was perceived as being destabilizing for the region.…”
Section: The Limitations Of Socializing Chinamentioning
confidence: 99%
“…These strategies can operate simultaneously and are not mutually exclusive. In fact, many authors have recently demonstrated that states employ a set of partially contradictory "hedging" strategies by diversifying their options and pursuing different approaches at the same time in order to decrease their security risks (Goh 2005(Goh , 2008(Goh , 2011aHeginbotham and Samuels 2002;Kuik 2008;Medeiros 2005;Tessman and Wolfe 2011).…”
Section: Rising Powers and Their Discontents: The Merits And Limits Omentioning
confidence: 99%
“…Binding (Ikenberry 2003;Rock 2000) Blackmailing (Lapp 2012;Walt 2005) Buck-passing (Chan 2010;Christensen and Snyder 1990;Mearsheimer 2001;Mochizuki 2007) Buffering (Gries 2005) Chain ganging (Christensen and Snyder 1990) Delegitimation (Walt 2005) Economic prebalancing (Layne 2006) Evasion (Bobrow 2008) Everyday and rightful resistance (Bobrow 2008;Destradi 2010;Ikenberry 2003;Ikenberry et al 2009;Prys 2010;Schweller and Pu 2011) Hedging (Goh 2005(Goh , 2008(Goh , 2011aHeginbotham and Samuels 2002;Kuik 2008;Medeiros 2005) Leash-slipping (Layne 2006) Log rolling (Ikenberry 2003) Niche diplomacy (Cooper 1997) Modification (Bobrow 2008) Omni-balancing (David 1991) Omni-enmeshment (Goh 2008) Pulling and hauling (Ikenberry 2003) Soft and indirect balancing (Goh 2008;Pape 2005;Paul 2005a)…”
Section: Competitivementioning
confidence: 99%
See 1 more Smart Citation